Pattern II and pattern III MS are entities distinct from pattern I MS: evidence from cerebrospinal fluid analysis - Jarius, Sven; Wildemann, Brigitte (Journal of neuroinflammation, 2017)
The diagnosis of multiple sclerosis (MS) is currently based solely on clinical and magnetic resonance imaging features. However, histopathological studies have revealed four different patterns of lesion pathology in patients diagnosed with MS, suggesting that MS may be a pathologically heterogeneous syndrome rather than a single disease entity.